Genetic and clinical spectrum of early growth response 2-related Charcot-Marie-Tooth disease in a Brazilian cohort - Cavalcanti, Eduardo Boiteux Uchôa; Santos, Savana Camilla de Lima; Couto, Christian Marques; Rocha, Galeno Vieira; Freitas, Maria Cristina Del Negro Barroso; Nascimento, Osvaldo José Moreira do (Arquivos de Neuro-Psiquiatria, 2025)
Background Charcot-Marie-Tooth (CMT) disease is a genetically diverse group of hereditary neuropathies. Most studies on the frequency of CMT subtypes report that the early growth response 2 (EGR2) gene accounts for less than 1% of cases. However, data regarding the epidemiology and clinical characteristics of EGR2-related CMT in Central and South America remain limited.Objective To characterize the clinical and genetic features of EGR2-related CMT in a Brazilian cohort.Methods We retrospectively analyzed clinical and ancillary data from four individuals with confirmed molecular diagnosis of EGR2-related CMT. Patients were categorized based on age of onset, motor nerve conduction velocity of the ulnar nerve, and nerve biopsy findings when available. Next-generation sequencing was utilized for genetic analysis.Results Pathogenic and likely pathogenic variants were identified exclusively in the three zinc-finger domains of EGR2, including a novel variant, c.1234G > C (p.Glu412Gln). Patients exhibited significant variation in clinical severity and phenotypes. Dysphagia, respiratory complications, and scoliosis were prominent features.Conclusion Our findings corroborate the complex and varied clinical presentations of EGR2-related CMT, highlighting respiratory issues and dysphagia as significant features. Comprehensive clinical assessment and early genetic diagnosis are essential for managing this condition's diverse phenotypic spectrum.
Keywords: Hereditary Sensory and Motor Neuropathy; Charcot-Marie-Tooth Disease; Early Growth Response Protein 2